Juan Ramón Jiménez y el mercado editorial - Sánchez García, Raquel (Dicenda. Estudios de lengua y literatura españolas, 2003)
This article analyses the links of Juan Ramón Jiménez with the world of publishing. The objective is to study the way that he followed to present his verses to the public: with which firms he signed a contract for his books, how he got the resources for it and what were the ways to distribute the books. I try to analyse a very common fact in writers of the first thirty years of the XX century: self-edition. The article approches too Juan Ramón Jiménez’s participation in some publishing houses. Juan Ramón Jiménez also was very interesed in typography and aesthetics of books, so that he tryed to control the process of printing all the time.